Construction of a Value Evaluation System for Fujian Tubao Architectural Heritage Based on Grounded Theory and the Analytic Hierarchy Process - Xiaoyang Qiao; Xinwei Liu; Wenliang Ye; Maowei Chen (Buildings)
Scientific evaluation of architectural heritage value constitutes a crucial foundation for advancing effective conservation practices and guiding policy development. Fujian Tubao, a distinctive form of defensive vernacular architecture found in southeastern China, integrates military defense, residential functions, and clan-based social organization into a unified spatial structure, making it an important component of China’s regional cultural heritage. In response to current challenges of inadequate preservation and progressive loss of heritage value associated with Fujian Tubao, there is an urgent need to establish a systematic evaluation framework to support and inform conservation efforts. This study centered on Fujian Tubao and proposed a comprehensive value assessment system that could innovatively integrate Grounded Theory with the Analytic Hierarchy Process (AHP). The Grounded Theory was first adopted to extract value dimensions of architectural heritage and their underlying connotations, thereby forming a value cognition system. Subsequently, the AHP was applied to assign quantitative weights and establish the priority order of each dimension, ultimately constructing a value evaluation system that could identify core objects for heritage conservation and clarify the hierarchy of their relative importance. This study achieved methodological integration in both the value extraction and evaluation stages, overcoming limitations of a single-method approach in dimension identification and weight assignment. The framework ensures logical consistency in value structuring and enhances the scientific validity of results. This study formulated a standardized and replicable evaluation framework tailored to the heritage value of Fujian Tubao. It also provides theoretical support for future conservation planning and offers a methodological reference for value assessment across diverse categories of architectural heritage.